Catalytic Stereoselective Multicomponent Reactions for the Synthesis of Spiro Derivatives: Recent Progress. Issue 45 (8th December 2022) - Patel, Divyang M.; Patel, Paras J.; Patel, Hitendra M.
Abstract: Spiro derivatives are important scaffolding substances found in many natural products and pharmaceuticals. In the last decade, numerous new approaches based on multicomponent reactions have been explored for the selective and efficient development of new spiro derivatives using various organocatalytic and transition metal‐based catalytic systems. This Review discusses pioneering advances in the field of catalytic stereoselective multicomponent reactions for the preparation of various spiro derivatives. These include stereoselective Michael cascade cyclization reactions, cycloadditions, diastereoselective reactions, and miscellaneous reactions for the synthesis of spiro‐hetero/carbocycles. Advances in the last decade have made it possible to synthesize various spiro compounds with good to excellent stereoselectivity under appropriate reaction conditions. However, achieving high regioselectivity in several described multicomponent reactions remains a challenge. Organocatalysts and transition‐metal‐based catalysts play a crucial role in achieving this milestone. Proposed catalytic mechanisms and supporting evidence are highlighted in this Review. The progress described in catalytic stereoselective approaches for spiro derivatives is immense. However, it is expected that new stereoselective synthetic methods will soon be developed that can be widely used for the preparation of spiro‐heterocycles/carbocycles. Abstract : The catalytic stereoselective synthesis of spiro compounds is a challenging task for organic chemists. This Review discusses recent advances in catalytic stereoselective, multicomponent reaction‐based methods for the synthesis of spiro compounds. Advantages, limitations, and mechanistic aspects are also highlighted.